Dinamika Stres, Strategi Coping, dan Dukungan Sosial yang Diharapkan Mahasiswa Skripsi di Universitas XYZ - Silvyana Hianto; Theresia Indira Shanti (Fakultas Psikologi Universitas Tarumanagara, 2018)
Thesis writing problem at XYZ University has emerged since a few years ago. Therefore, this study aims to understand the existing conditions in the field regarding stress conditions, causes, coping strategies, and expected social support. This research uses the mixed methodology, involving XYZ University students who cannot complete their thesis in two semesters (including “Seminar”). Based on data from 84 students who participated, is known that the main obstacles are difficult in writing down ideas to a scientific form, bad relationship with the thesis advisor, courses that should be taken, and emergency psychological disorders symptoms. Furthermore, the most used coping strategy is emotional-focused coping. While the most expected social support is emotional support, networking (e.g., study groups) and information (e.g., feedback, discussion, and suggestions), qualitative data shows that